ZONING MAP OF TERRITORY UKRAINE ACCORDING TO THE RESULTS OF SEROLOGICAL MONITORING STUDIES TESCHEN DISEASE IN THE POPULATION OF WILD BOARS - Ситюк, М. П.; Безименний, М. В. (Scientific Progress & Innovations, 2014)
The results of serological monitoring of wild pigs concerning Teschen disease in the context of rayons (districts) of Ukraine are described. 6840 blood sera samples were collected from hunter-killed boars during 2001-2013 hunting seasons in 374 rayons in all oblasts of Ukraine. We used micromethod of neutralization test in a fetal pig kidney cell culture. As a result of the retrospective monitoring we mapped rayons where samples were collected and where positive serum samples were identified from.